Bulk Atmospheric Deposition of Major Ions and Dissolved Organic Nitrogen in the Lower Course of a Tropical River Basin, Southern Bahia, Brazil - Araujo, Taiana G.; Souza, Marcelo F. L.; Mello, William Z. de; Silva, Daniela M. L. da (Journal of the Brazilian Chemical Society, 2015)
Major ionic constituents (Cl – , Na + , K + , Mg 2+ , Ca 2+ , NH 4 + , NO 3 – , SO 4 2– ) and dissolved organic nitrogen were determined, from September 2009 to January 2010, in bulk atmospheric deposition in the lower course of Cachoeira River, southern Bahia, Brazil, where studies on this theme are still absent. The high fluxes of Na+, Mg2+ and Cl– observed in the innermost sampling site evidence the continuity of marine influence in the atmosphere of the city of Itabuna. Concentrations of H + , Ca 2+ , SO 4 2– and NO 3 – denoted non-marine anthropogenic sources. The contributions of dissolved organic and inorganic nitrogen were different between the evaluated sites. This region is still subject to little impact by anthropogenic emissions compared to other urban areas in Brazil, according to estimates of atmospheric fluxes of SO 4 2– , NO 3 – and NH 4 + .